Poland in the European Union Single Market - Pasimeni Paolo (Studia Ekonomiczne i Regionalne, 2021)
Subject and purpose of work: This paper studies the process of integration of Poland in the EU Single Market. It makes use of official statistics from a wide range of institutions (IMF, OECD, Eurostat, and Statistics Poland) in order to define structural patterns, shedding light on the overall integration of the country with the rest of the world.